Volume 1: Aircraft Engine; Marine; Turbomachinery; Microturbines and Small Turbomachinery 2001
DOI: 10.1115/2001-gt-0302
|View full text |Cite
|
Sign up to set email alerts
|

Wake-Wake Interactions and its Potential for Clocking in a Transonic High Pressure Turbine

Abstract: Two-dimensional unsteady Navier-Stokes calculations of a transonic single stage high pressure turbine were carried out with emphasis on the flow field behind the rotor. Detailed validation of the numerical procedure with experimental data showed excellent agreement in both time-averaged and time-resolved flow quantities. The numerical time-step as well as the grid resolution allowed the prediction of the Kármán vortex streets of both stator and rotor. Therefore the influence of the vorticity shed from the stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
1
8
1
Order By: Relevance
“…In other words, the intensity and the locations of static pressure gradients at the exit of the rotor changes according to the location of the rotor in the first stator pitch. This was also observed in numerical simulations (see for example Hummel [2]; Marconcini and Pacciani [18]). These pressure gradients are expected to play a dominant role in the rotor-second stator interaction.…”
Section: Rotor-stator Interactionsupporting
confidence: 71%
See 2 more Smart Citations
“…In other words, the intensity and the locations of static pressure gradients at the exit of the rotor changes according to the location of the rotor in the first stator pitch. This was also observed in numerical simulations (see for example Hummel [2]; Marconcini and Pacciani [18]). These pressure gradients are expected to play a dominant role in the rotor-second stator interaction.…”
Section: Rotor-stator Interactionsupporting
confidence: 71%
“…The surface heat flux is determined thanks to the temperature evolution during the test. Knowing the thermal properties of the ceramic substrate (Ma cor, 2 0.5 ρCk = 2073J m Ks , from Dénos [26]) and applying the mono-dimensional unsteady conduction equation (1), it is possible to determine the temperature profile in the insulating layer at each time step.…”
Section: Heat Transfer Measurement Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further behaviour of the stator and rotor wakes can be observed in Fig. 4 being a compilation of the results presented in [23][24][25][26][27]. All wakes leave the rotor moving, generally, in the direction of the main flow velocity w 2 .…”
Section: Wake Deformation and Physical Nature Of Clockingmentioning
confidence: 84%
“…Some initial attempts to take into account vortex dynamics when analysing the stator wake motion through the rotor cascade have been published. A most detailed study was done by Kost et al [23], Tiedemann and Kost [24] and Hummel [25], who examined experimentally and numerically unsteady flow fields generated by stator wakes in rotor passages of a full size aero-engine high-pressure turbine stage having 43 stator blades and 64 rotor blades. Visual studies of the flow inside the rotor passages performed by Kost et al with the aid of coolant injected to the flow at the vicinity of stator blade trailing edges have revealed that on its way through the rotor passage the stator wake forms two separate areas of different-sign vorticity which move one after the other through the passage, thus creating the earlier mentioned negative jet between the blade walls, clearly observed on the numerically calculated distributions of velocity vectors.…”
Section: Wake Deformation and Physical Nature Of Clockingmentioning
confidence: 99%